Metacognitive Knowledge and Mathematics Engagement Among Senior High School Students: Mediating Role of Cognitive Flexibility - Gyimah, Isaac Osei; Ackon, John; Frimpong, Kingsley Owusu (International Journal of Mathematics and Mathematics Education, 2026)
Purpose – The study aimed to investigate the impact of metacognitive knowledge on senior high school students’ engagement in mathematics and to explore cognitive flexibility as a mediating variable. The study addresses the ongoing disengagement in mathematics and the need to understand the cognitive processes that facilitate active learning. Methodology – The study used a quantitative cross-sectional survey of 341 students from three senior high schools in Ghana. Participants were selected using both stratified and simple random sampling. Findings – Metacognitive knowledge did not directly influence engagement in mathematics, but it did positively influence cognitive flexibility. Furthermore, cognitive flexibility positively affected engagement. Cognitive flexibility fully mediated the effect of metacognitive knowledge on mathematics engagement (β = 0.393, p < 0.001). Novelty – This study provides a novel empirical contribution by demonstrating the full mediating role of cognitive flexibility in the relationship between metacognitive knowledge and mathematics learning engagement. Significance – This study is helpful for teachers, curriculum developers, and educational researchers in designing mathematics learning strategies that emphasize the development of students' cognitive flexibility. Significance – This study also contributes to the evidence from Ghana by demonstrating that engagement in mathematics depends on cognitive flexibility to supplement metacognitive knowledge, thereby providing valuable insight into the psychological mechanisms underlying mathematics learning.